A versatile modular vector set for optimizing protein expression among bacterial, yeast, insect and mammalian hosts. - Márk Somogyi; Tamás Szimler; Attila Baksa; Barbara M Végh; Tamás Bakos; Katalin Paréj; Csaba Ádám; Áron Zsigmond; Márton Megyeri; Beáta Flachner; Ráchel Sajó; Éva Gráczer; et al. (PLoS ONE)
We have developed a unified, versatile vector set for expression of recombinant proteins, fit for use in any bacterial, yeast, insect or mammalian cell host. The advantage of this system is its versatility at the vector level, achieved by the introduction of a novel expression cassette. This cassette contains a unified multi-cloning site, affinity tags, protease cleavable linkers, an optional secretion signal, and common restriction endonuclease sites at key positions. This way, genes of interest and all elements of the cassette can be switched freely among the vectors, using restriction digestion and ligation without the need of polymerase chain reaction (PCR). This vector set allows rapid protein expression screening of various hosts and affinity tags. The reason behind this approach was that it is difficult to predict which expression host and which affinity tag will lead to functional expression. The new system is based on four optimized and frequently used expression systems (Escherichia coli pET, the yeast Pichia pastoris, pVL and pIEx for Spodoptera frugiperda insect cells and pLEXm based mammalian systems), which were modified as described above. The resulting vector set was named pONE series. We have successfully applied the pONE vector set for expression of the following human proteins: the tumour suppressor RASSF1A and the protein kinases Aurora A and LIMK1. Finally, we used it to express the large multidomain protein, Rho-associated protein kinase 2 (ROCK2, 164 kDa) and demonstrated that the yeast Pichia pastoris reproducibly expresses the large ROCK2 kinase with identical activity to the insect cell produced counterpart. To our knowledge this is among the largest proteins ever expressed in yeast. This demonstrates that the cost-effective yeast system can match and replace the industry-standard insect cell expression system even for large and complex mammalian proteins. These experiments demonstrate the applicability of our pONE vector set.